Urdu ka guldasta Nargis grade 4 - Farooqui, Fozia Ahsan (Karachi : Oxford university press, 2020)
Urdu ka Guldasta Nargis is a collection of classic Urdu poetry that showcases the beauty and depth of the language. The book features a selection of poems, ghazals, and verses by renowned poets, presenting themes of love, philosophy, nature, and human emotions. The title, "Nargis" (which refers to the narcissus flower), symbolizes beauty and elegance, reflecting the aesthetic qualities of the poetry in the book. The collection is designed to introduce readers to the richness of Urdu literature, making it accessible to both new readers and those familiar with the language.
Keywords: Urdu : Textbook